Enhancement of power quality based on dynamic voltage restorer matrix inverter-sliding mode control scheme - Soomro, Abdul Hameed; Larik, Abdul Sattar; Mahar, Mukhtiar Ahmed; Sahito, Anwer Ali; Koondhar, Mohsin Ali; Kim, Yun-Su; Alaas, Zuhair Muhammed; Touti, Ezzeddine; Ahmed, M.M.R. (Electric power systems research, 2025)
•Matrix inverter-based DVR is used enhances power quality by mitigating voltage sags.•Sliding mode control (SMC) is used to ensure robust and accurate voltage restoration.•Compact, cost-effective design with fewer components compared to traditional DVRs.•Real-time detection and compensation of voltage sags has been analyzed to protect sensitive loads.•Reduces total harmonic distortion (THD) and improves voltage stability has been analyzed. This paper introduces a novel application of a three-phase matrix converter for Dynamic Voltage Restorers (DVRs), which is capable of direct AC-AC power conversion without the need for an energy storage component. Motivated by the need for efficient and responsive voltage sag correction, a sliding mode controller (SMC) with a Proportional-Integral (PI) sliding surface and hysteresis control is proposed. To optimize the PI gains of the SMC, traditional methods such as the real-coded genetic algorithm were considered; however, these methods typically involve extended convergence times. The Ant Colony Optimization (ACO) technique was employed, resulting in optimal PI gains of 6.87688 and 0.850851. The effectiveness of the SMC was validated under conditions of faults and load variations demonstrating satisfactory performance and stabilization at the onset of voltage sags. Numerical analysis reveals that the SMC maintains a THD % of 2.24 % adhering to the IEEE standard 519–1992. The DVR's performance, empowered by the matrix converter with the SMC framework, has been thoroughly analyzed, and the THD % was further scrutinized using the Fast Fourier Transform. This research confirms the matrix converter integrated with SMC as a robust solution for dynamic voltage restoration, providing a promising avenue for enhancing power quality in modern distribution networks.